IoT-Based Water Quality Sensor Node with Cloud Storage and Iterative Dashboard - CHOONG, JUN AN; BAHARI, AZLINA BINTI; AB GHAFAR, AIMI SYAMIMI BINTI; ISMAIL, MUHAMMAD FAIZAL BIN (Progress in Engineering Application and Technology, 2026)
This paper presents the development of an IoT-based river water quality monitoring system integrated with cloud storage and an interactive dashboard for real-time analysis. In this context, a Heltec WiFi LoRa32-V3 microcontroller was applied with various water quality sensors such as pH, turbidity, temperature, dissolved oxygen and total dissolved solids. Sensor data transmitted by LoRaWAN to The Things Network are processed using Node-RED, stored in a cloud-based MySQL database and then visualized on a Grafana dashboard. Field testing carried out at Sungai Panchor, Muar, Johor attested to the reliable transmission of data, effective cloud integration and clear visualization in real time. The proposed system offers a scalable, cost-effective and efficient solution for the continuous monitoring of the quality of river water.